Empowering Teachers to Promote Inclusive Education - European Agency for Special Needs and Inclusive Education (Zenodo, 2015)
In 2015, the Agency worked on behalf of the United Nations Educational, Scientific and Cultural Organization (UNESCO) to provide a suite of materials on empowering teachers. The results of this work have been summarised in three documents: a literature review, a case study and a methodology overview. The case study looks at practice examples from 13 Agency member countries: Austria, Belgium (Flemish community), Cyprus, Finland, Germany, Iceland, Ireland, Latvia, Norway, Portugal, Sweden, United Kingdom (England) and United Kingdom (Scotland), with additional country/policy information from France, Malta, United Kingdom (Northern Ireland) and United Kingdom (Wales). The study considers implications for wider policy development, teacher education and professional development and the development of teacher educators. The methodology outlines the conceptual framework for this work, as well as the purpose of and the relationship between the case study documents. Download the case study and the methodology overview in English below. The literature review is available here . This publication has been funded with support from the European Commission. This publication reflects the views only of the author, and the Commission cannot be held responsible for any use which may be made of the information contained therein.